Galen - Jerzy Supady (Health Promotion & Physical Activity, 2020)
After Hippocrates, Galen was one of the most outstanding physicians of the ancient world. He was born in Pergamon in c. 131 AD, but soon upon completion of his medical studies he went to become physician-in-ordinary to the Roman Emperors. Being devoted to his studies, he made a lot of discoveries in the field of anatomy and physiology. In pathology, he based his ideas on Hippocrates teaching. In diagnostics, he examined pulse and urine. He wrote about 500 treatises of which only 117 writings have survives to this day. Galen’s scientific achievements have contributed enormously to the development and progress of medical sciences. His authority was unquestionable in Europe for over 15 centuries. Galen died in Rome in c. 201 AD.